Komunikasi Efektif dalam Pembelajaran Pendidikan Jasmani, Kesehatan, dan Rekreasi: Peran Bahasa Indonesia sebagai Bahasa Pengantar - Ika Febriana; Agil Hagaini Hulu; Firyal Salsabila; Khairul Adzmi Fathurrahman (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research aims to explore effective communication in Physical Education, Health and Recreation learning, with a focus on the role of Indonesian as an essential language of instruction. The method used was a questionnaire distributed to several Medan State University students to collect data regarding their perceptions regarding the clarity of instructions, understanding of the material, and its impact on learning motivation. The questionnaire consists of 20 questions to measure students' level of agreement with various aspects of communication in learning. The results of data analysis showed that 96.5% of respondents felt that clear and effective communication from teachers greatly contributed to understanding the subject matter and significantly increased their motivation in attending class. These findings confirm that good and correct use of Indonesian is very important in creating a more interactive and effective learning environment in the fields of Physical Education, Health and Recreation. It is hoped that this research can provide insight for teachers and educators about the importance of communication strategies in improving the quality of learning.